1987
DOI: 10.1111/j.1469-7610.1987.tb01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Problems in Children With Diabetes as a Function of Sex and Age of Onset of Disease

Abstract: Twenty-seven children with early onset (less than or equal to 3 years) diabetes (EOD), 24 with late onset (greater than or equal to 4 years) diabetes (LOD) and 30 sibling controls were compared on measures of psychosocial adjustment. These included parent rating scales of behaviour problems and temperament; direct measures of self-esteem, body image and school achievement; and indices of diabetic control. Results indicated that LOD boys showed increased incidence of behaviour problems, 83% of whom could be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
27
2
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 42 publications
6
27
2
1
Order By: Relevance
“…Several studies have raised concerns about the effects of diabetes on memory and learning in children [2,16,17,18]. Additionally, memory impairment has been observed in older adults with diabetes [19] and in diabetics with hypertension [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have raised concerns about the effects of diabetes on memory and learning in children [2,16,17,18]. Additionally, memory impairment has been observed in older adults with diabetes [19] and in diabetics with hypertension [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these behaviors can also interfere with diabetes selfmanagement. Females are more likely to participate in diabetes mismanagement, whereas boys are more likely to engage in risky behaviors (227,233,234). Alcohol use is a particular problem, as it can be associated with severe hypoglycemia several hours after drinking, if adequate food is not ingested.…”
Section: Recommendationmentioning
confidence: 99%
“…For example, Littlefield et al (9) found that adolescent girls not only exhibited poorer overall treatment compliance and metabolic control than boys, but that girls with poorer adherence also reported lower self-esteem, less self-efficacy, and more depressive symptoms. However, other studies (8,10,17) using similar methodologies have failed to demonstrate significant links between metabolic control and aspects of the self. In part, these inconsistent findings may result from the failure to consider the moderating role of gender on self-identity formation during adolescence.…”
mentioning
confidence: 99%
“…Compared with boys, girls have been shown to exhibit a constant increase in mean HbA 1c , with an estimated increase from pre-to postpuberty of 0.92% (6). Also, girls tend to be more distressed by diabetes (8), to exhibit higher rates of overall mismanagement of their diabetes (9) with less adherence to their diabetes meal plan during periods of stress (10), and to experience greater depressive and eating disorder symptoms, both of which are linked to poor metabolic control (9,11). Thus, there is a need to identify specific risk factors for poor metabolic control in girls.…”
mentioning
confidence: 99%